Stretching after spinal cord injury: a call for evidence for this common clinical practice - Williams, Todd E.; DeMark, Louis A.; Olarewaju, Tinuade A.; Hawkins, Kelly A.; Fox, Emily J. (Frontiers in Rehabilitation Sciences, 2024)
Stretching is a ubiquitous rehabilitation intervention for individuals with spinal cord injury (SCI), intended to reduce spasticity, maintain or improve joint range of motion, and prevent joint contractures. Although people with SCI report that stretching is their preferred approach to reduce spasticity, limited evidence supports the use of stretching for people with SCI, including short-term (< one hour) effects on spasticity. Further, the long-term effects and the effects of stretching on motor function have yet to be examined in humans with SCI. Evidence from pre-clinical studies in rats with SCI demonstrates that stretching impairs motor output, reduces spinal cord excitability, and abolishes walking function. This perspective paper discusses evidence of static stretching in humans and rats with SCI regarding the effects on range of motion, joint contractures, and effects on voluntary and involuntary (i.e., spasticity) motor output. Additionally, we aim to challenge assumptions regarding the use of stretching and encourage research to advance the understanding of this common rehabilitation approach. Research is needed to investigate underlying mechanisms of stretch-induced effects and to advance stretching protocols to optimize the potential beneficial effects of stretching for people with SCI.